Pupils' views of mathematics teaching in Finland and Tatarstan - Pehkonen, Erkki; Safuanov, Ildar (NOMAD Nordic Studies in Mathematics Education, 1996)
The focus of this comparative survey was the following research questions: What are pupils' views of mathematics teaching in each country? What are the differences and similarities in these views between pupils in Finland and in Tatarstan, Russia ? In this study, data were gathered with the help of a questionnaire. The questionnaire consists of 32 structured statements about mathematics teaching for which the pupils were asked to rate their views on a 5-step scale. The Finnish sample comprised255pupils,andtheTatarsample206pupils. Ourdatahasbeengathered with a non-probabilistic convenience sampling. The main results of our survey are, as follows: Generally, pupils' views of mathematics teaching and learning in Finland and Tatarstan are rather far from similar. An investigation of the differences between pupils' answers across the two countries also showed views that are characteristic for each country. For pupils in Tatarstan, the most characteristic might be the following views: the importance of exact reasoning and explanations, and the value of making strong demands on pupils. For pupils in Finland, the characteristic views seem to be as follows: a calculation orientation in learning mathematics, and the value of strict discipline and of depending on the teacher. When discussing problem orientation, we may conclude that in both countries mathematics teaching is striving toward a problem orientation, but with a different emphasis. In the case of independent work, the results seem to indicate that the orientation in question for pupils both in Finland and in Tatarstan is similar, but not very strongly favored. The pupils' views of the demands on them and on their teachers in mathematics seem to be much stronger in Tatarstan than in Finland.